The effects of larynx height on vowel production are mitigated by the active control of articulators. (May 2019) - Janssen, Rick; Moisik, Scott R.; Dediu, Dan
Highlights: Larynx height affects vowel production. Nevertheless, these effects are mitigated by the other articulators. Modern human larynx height seems optimized for speech production. But deviations from this height do not preclude speech. Abstract: The influence of larynx position on vowel articulation is an important topic in understanding speech production, the present-day distribution of linguistic diversity and the evolution of speech and language in our lineage. We introduce here a realistic computer model of the vocal tract, constructed from actual human MRI data, which can learn, using machine learning techniques, to control the articulators in such a way as to produce speech sounds matching as closely as possible to a given set of target vowels. We systematically control the vertical position of the larynx and we quantify the differences between the target and produced vowels for each such position across multiple replications. We report that, indeed, larynx height does affect the accuracy of reproducing the target vowels and the distinctness of the produced vowel system, that there is a "sweet spot" of larynx positions that are optimal for vowel production, but that nevertheless, even extreme larynx positions do not result in a collapsed or heavily distorted vowel space that would make speech unintelligible. Together with other lines of evidence, our results support the view that the vowel space of human languages is influenced by our larynx position, but that other positions of the larynx may also be fully compatible with speech.